Perspectives and challenges for the use of radar in biological conservation - Hüppop, O.; Ciach, M.; Diehl, R.; Reynolds, D.; Stepanian, P.; Menz, Myles (Blackwell Publishing, 2019)
Radar is at the forefront for the study of broad-scale aerial movements of birds, bats and insects and related issues in biological conservation. Radar techniques are especially useful for investigating species which fly at high altitudes, in darkness, or which are too small for applying electronic tags. Here, we present an overview of radar applications in biological conservation and highlight its future possibilities. Depending on the type of radar, information can be gathered on local- to continental-scale movements of airborne organisms and their behaviour. Such data can quantify flyway usage, biomass and nutrient transport (bioflow), population sizes, dynamics and distributions, times and dimensions of movements, areas and times of mass emergence and swarming, habitat use and activity ranges. Radar also captures behavioural responses to anthropogenic disturbances, artificial light and man-made structures. Weather surveillance and other long-range radar networks allow spatially broad overviews of important stopover areas, songbird mass roosts and emergences from bat caves. Mobile radars, including repurposed marine radars and commercially dedicated ‘bird radars’, offer the ability to track and monitor the local movements of individuals or groups of flying animals. Harmonic radar techniques have been used for tracking short-range movements of insects and other small animals of conservation interest. However, a major challenge in aeroecology is determining the taxonomic identity of the targets, which often requires ancillary data obtained from other methods. Radar data have become a global source of information on ecosystem structure, composition, services and function and will play an increasing role in the monitoring and conservation of flying animals and threatened habitats worldwide.